Retraction notice to ‘Subversion of immunity by schistosomes’. [ Microbiology Australia 2013, 34(3), 137–141. doi:10.1071/MA13046] - Bernd Kalinna; Anna Walduck (Microbiology Australia, 2015)
After due consideration, the editors of the journal and the authors of the paper agree that the paper be retracted from Microbiology Australia . Reason: irresolvable authorship dispute.